Improvement study on internal supply chain system in offshore industry - Chen, Lin (2014)
The construction of jack-ups drilling rigs requires careful planning and execution to achieve a short turnaround time (TAT) to remain competitive in the industry. This project aims to study the internal supply chain network of planning and execution of steel material flow. The objective is to optimize the supply chain network so as to generate cost savings or reduce cycle time. In tactical level, the current procurement strategy and inventory management were revised to achieve 95% service level and accomplish more cost-effective decision. Concept of material standardization was proposed to reduce demand variability and average inventory level in the shipyard. To reduce lateness in the delivery of blasted raw steel plates to the panel fabrication line, the idea of balancing the blasting capacity was introduced to improve blasting service level. Lastly, in the operational level, the study on panel fabrication flow line main production facility was carried out via discrete event simulation technique. Investigations on feasible improvement efforts to the panel fabrication line system suggested that implementation of Single-Side Welding machine is the most promising and cost effective improvement, which is predicted to increase the daily panel throughput by 35%.